Representation of cultural values in Tempuutn Senarikng of Dayak Benuaq and Tunjung tribes - Putri, Nina Queena H. (HTS teologiese studies, 2023)
Tempuutn Senarikng is one Indonesian mythical folklore telling the origins of humans in the Dayak Benuaq and Tunjung tribal communities. This research aims to represent the cultural values in Tempuutn Senarikng . This study is qualitative research using an ethnographic approach and interactive model data analysis techniques. The results show that Tempuutn Senarikng contains cultural values of the Dayak Benuaq and Tunjung tribal communities explaining that (1) the nature of the Dayak Benuaq and Tunjung people’s life is to try to avoid being cursed by praying and performing ceremonial rituals. (2) The nature of the work of the Dayak Benuaq and Tunjung tribes is oriented to being a living. The work commonly carried out by the Dayak Benuaq and Tunjung people is farming. (3) Human nature in space and time is oriented to the future so what they do now will also have an impact on the future. However, they do not forget the past as part of life lessons. Therefore, they always make offerings in the form of sacrificial animal blood and cooked food in every ceremony to be grateful for what they have obtained in life, to avoid disaster, and to facilitate all hopes. (4) The nature of human relations with nature is by always maintaining harmony. They always conduct various ceremonial activities to get rid of disturbing spirits from human life, and vice versa, they are always accompanied by good spirits. In other words, the folklore of Tempuutn Senarikng is the forerunner of the traditions and culture of the Dayak Benuaq and Tunjung tribal communities continuing to be undertaken to this day. Contribution : The article results can be used in scientific research in verbal literature, folklore, and ethnology fields.